Examining the association between body mass index and abnormal uterine bleeding: a cross-sectional study among women in a tertiary care gynaecology outpatient setting - Verma, Reema; Horo, Usha Madhulika; Singh, Shashi Bala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: This study examines body mass index (BMI) and abnormal uterine bleeding (AUB) in tertiary care hospital gynaecology outpatients. The findings will improve resource-limited AUB management practices. Methods: At Rajendra Institute of Medical Science in Ranchi, India, 100 women aged 18-60 attended the gynaecology outpatient department for this cross-sectional study. Clinical assessments, BMI measurements and PALM-COEIN-based diagnostic techniques classified abnormal uterine bleeding (AUB) categories in participants. Results: Higher BMI categories were associated with more AUB, according to the study. Obese women had the greatest AUB rate (83.3%), followed by overweight (66.7%). Obese subjects had the highest AUB-related ovulatory dysfunction. Women with higher BMI had more frequent heavy menstrual flow (p<0.01). Conclusions: Elevated BMI is strongly associated with an increased prevalence of abnormal uterine bleeding, particularly in overweight and obese women.